Seasonal patterns of shell flux, δ18O and δ13C of small and large N. pachyderma (s) and G. bulloides in the subpolar North Atlantic. (25th March 2013) - Jonkers, Lukas; van, Steven; Zahn, Rainer; Peeters, Frank J.C.
Abstract [1] Past water column stratification can be assessed through comparison of the δ18O of different planktonic foraminiferal species. The underlying assumption is that different species form their shells simultaneously, but at different depths in the water column. We evaluate this assumption using a sediment trap time‐series of Neogloboquadrina pachyderma (s) and Globigerina bulloides from the NW North Atlantic. We determined fluxes, δ18O and δ13C of shells from two size fractions to assess size‐related effects on shell chemistry and to better constrain the underlying causes of isotopic differences between foraminifera in deep‐sea sediments. Our data indicate that in the subpolar North Atlantic differences in the seasonality of the shell flux, and not in depth habitat or test size, determine the interspecies Δδ18O. N. pachyderma (s) preferentially forms from early spring to late summer, whereas the flux of G. bulloides peaks later in the season and is sustained until autumn. Likewise, seasonality influences large and small specimens differently, with large shells settling earlier in the season. The similarity of the seasonal δ18O patterns between the two species indicates that they calcify in an overlapping depth zone close to the surface. However, their δ13C patterns are markedly different (>1‰). Both species have a seasonally variable offset from δ13CDIC that appears to be governed primarily by temperature, with larger offsets associated with higher temperatures. The variable offset from δ13CDIC implies that seasonality of the flux affects the fossil δ13C signal, which has implications for reconstruction of the past oceanic carbon cycle.